Modified mattress sutures vs running sutures in uterine closure: which is better? - Shah, Swar S.; Shah, Jayneel V.; Valia, Shivani A.; Patel, Uday J. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Conventional closure of uterus has been known to bear risk of scar dehiscence and scar rupture in subsequent pregnancies and thus, a study was conducted to compare the outcome of uterine closure with modified mattress manner and running manner and to establish a better method of uterine closure during caesarean section. Objective was to compare the conventional single layer running sutures and single layer modified mattress sutures for closure of uterus in caesarean section and find out which method is superior. Methods: This prospective interventional study was carried out in Dhiraj Hospital, a tertiary care hospital in Vadodara. 60 pregnant women in the study criteria were equally divided randomly into 2 groups. Uterine closure was done in single layered sutures, one by running sutures and other group by modified mattress sutures. Results: Uterine scar thickness on 8th day and 6 months post-operatively was significantly more in single layered suturing by modified mattress suture compared to running suture (p <0.05). Conclusions: Uterine closure by single layered modified mattress suture is better in comparison to conventional single layer running suture.